Perception of Nurses' Support among Family Members of Hospitalized Patients in A Tertiary Health Facility in South-West, Nigeria - Cecilia Bukola Bello PhD, MSc, BNSc, RN, RM, RPHN; Oluwasayo Bolarinwa Ogunlade PhD, RN; Deborah Tolulope Esan PhD, MPH, BNSc, RN, RM, RPHN; Olasupo Augustine Ijabadeniyi PhD, MPH, LLB, BL, BSc; Adebanke Covenant Bello RN (SAGE Publishing, 2023)
Introduction Family members of hospitalized patients are often faced with challenges and may experience difficulty in coping without appropriate support. The aim of this study was to assess hospitalized patients' family members' perception of nurses' support. Methods A cross-sectional descriptive design was utilized. A total of 138 family members of hospitalized patients in a tertiary health facility were selected using a purposive sampling technique. Data were collected with an adopted structured questionnaire. Analyses of data were performed using frequency, percentage, mean, standard deviation, and multiple regression. The level of significance was set at 0.05 ( p < .05. Also, age, gender, and type of family were the predictors of emotional support ( R 2 = 84, F (6, 131) = 5.92, p < .05. Results The mean score of cognitive support was 9.92, emotional support was 15.59 while the overall mean score was 39.42. More than half (60.9%) reported that nurses never and rarely provided available and easy-to-read literature about the health problem of their patient (Mean = 2.30 ± 1.00). More than half (58.0%) reported that nurses never and rarely provided ideas, information and thoughts in a manner that allowed family members to think and learn. (Mean = 2.27 ± 0.98). About 1 out of 3 reported poor perception of cognitive support. While less than half (45.7%) reported poor perception of emotional support. Age, gender and relationship were predictors of cognitive support (R2 = .63, F (6,131) = 4.46, p < 0.05). Also, age, gender and type of family were the predictors of emotional support (R2 = .84, F (6,131) = 5.92, p < 0.05). Conclusion A significant number of families of hospitalized patients reported poor perception of cognitive, emotional, and overall support from nurses. Adequate staffing is a prerequisite for effective family support. Nurses also need appropriate training in providing family support. The focus of family support training should emphasize practices that nurses can use in everyday interactions with patients and family members.